2017
DOI: 10.1175/mwr-d-16-0457.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Dryline Convection Forecasts to Upstream Forecast Errors for Two Weakly Forced MPEX Cases

Abstract: The sensitivity of convective forecasts along the Texas dryline to upstream forecast fields at earlier lead times is evaluated for two consecutive days (27-28 May) characterized by no clear synoptic forcing for convection initiation (CI) during the 2013 Mesoscale Predictability Experiment (MPEX) by applying the ensemble-based sensitivity technique to convection-allowing WRF ensemble forecasts. For both cases, the members with stronger convection are characterized by higher water vapor just above the top of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Recent studies by Schneider et al (2019) and Keil et al (2019) have also shown that different assumptions for the number of cloud condensation nuclei could be included in convective-scale ensemble forecasting but only if the model employs a double-moment microphysics scheme. Because of the fundamental uncertainties in the simulations due to nonlinearities of the model equations, several studies have noted the significant impact of initial boundary conditions (IBCs) and lateral boundary conditions (LBCs) on the simulation of convective precipitation for some situations (e.g., Hohenegger et al, 2006;Trentmann et al, 2009;Richard et al, 2011;Bouttier and Raynaud, 2018) and that ensemble members with the most accurate initial and boundary conditions are most skillful at predicting the location of convective initiation (Barrett et al, 2015). One common approach for accounting for uncertainties in the initial and boundary conditions is that perturbations entering the model from the lateral boundaries can be provided by different driving ensemble prediction system (EPS) members as is the case for COSMO-LEPS (Montani et al, 2011) or COSMO-DE-EPS (Gebhardt et al, 2011;Kühnlein et al, 2014).…”
Section: Comparison Of Methods To Perturb Initial and Boundary Conditionsmentioning
confidence: 99%
“…Recent studies by Schneider et al (2019) and Keil et al (2019) have also shown that different assumptions for the number of cloud condensation nuclei could be included in convective-scale ensemble forecasting but only if the model employs a double-moment microphysics scheme. Because of the fundamental uncertainties in the simulations due to nonlinearities of the model equations, several studies have noted the significant impact of initial boundary conditions (IBCs) and lateral boundary conditions (LBCs) on the simulation of convective precipitation for some situations (e.g., Hohenegger et al, 2006;Trentmann et al, 2009;Richard et al, 2011;Bouttier and Raynaud, 2018) and that ensemble members with the most accurate initial and boundary conditions are most skillful at predicting the location of convective initiation (Barrett et al, 2015). One common approach for accounting for uncertainties in the initial and boundary conditions is that perturbations entering the model from the lateral boundaries can be provided by different driving ensemble prediction system (EPS) members as is the case for COSMO-LEPS (Montani et al, 2011) or COSMO-DE-EPS (Gebhardt et al, 2011;Kühnlein et al, 2014).…”
Section: Comparison Of Methods To Perturb Initial and Boundary Conditionsmentioning
confidence: 99%
“…I do have some concerns regarding the motivation and methodology for this work. While the authors motivate the work as a worthwhile approach to improve convectionallowing model (CAM) forecasts, effectively creating sufficient spread across the forecast distribution, I struggle to see the benefit of this domain-shifting approach over other well-documented lateral boundary perturbation techniques (e.g., Torn et al 2016), and I don't feel the author's sufficiently demonstrated this benefit in the introduction. Additionally, I believe the authors try to attribute the forecast variability to their methodology (i.e., domain shifting), but I do not feel there is substantial corroborating evidence to support this conclusion.…”
mentioning
confidence: 99%
“…Sensitivity approaches such as those demonstrated by Schumacher and Davis (2010) and Ancell and Hakim (2007) could be valuable additions to the analysis. I invite the authors to consult a number of papers that apply sensitivity analyses to convection-resolving forecasts as well: Bednarczyk and Ancell (2015), Hill et al (2016), Limpert and Houston (2018), and Torn et al (2016). Additionally, other aspects of predictability could be garnered through initializing ensemble forecasts at later times, which may answer the particular question of whether CI is the limiting factor of predictability.…”
mentioning
confidence: 99%
See 2 more Smart Citations